2011
DOI: 10.2174/1874120701105010001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of Metformin for the Treatment of Type II Diabetes Mellitus

Abstract: Metformin is an antihyperglycemic agent commonly used for the treatment of Type II diabetes mellitus. However, its effects on patients are derived usually from clinical experiments. In this study, a dynamic model of Type II diabetes mellitus with the treatment of metformin is proposed. The Type II diabetic model is a modification of an existing compartmental diabetic model. The dynamic simulation of the metformin effect for a Type II diabetic patient is based on the pharmacokinetic and pharmacodynamic relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…The LSS model was further validated using data from 16 previously published studies . The results (Table , Figure , Supplementary Figures S7 and S8) indicated that the AUC(0,24 h) predicted by the two point LSS model was in excellent agreement ( r 2 = 0.976, bias −1.0%, precision 4.3%) with the corresponding AUC(0,24 h) best estimates, over a wide range (3.8–22.4 μg h l −1 ) of AUC(0,24 h) values and under a variety of demographic, experimental and clinical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The LSS model was further validated using data from 16 previously published studies . The results (Table , Figure , Supplementary Figures S7 and S8) indicated that the AUC(0,24 h) predicted by the two point LSS model was in excellent agreement ( r 2 = 0.976, bias −1.0%, precision 4.3%) with the corresponding AUC(0,24 h) best estimates, over a wide range (3.8–22.4 μg h l −1 ) of AUC(0,24 h) values and under a variety of demographic, experimental and clinical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A Sorensen-modellt a közelmúltban NIDDM-páciensekre is adaptálták [6]. Sun és mtsai a metformin részletes farmakokinetikai-farmakodinamikai (PK-PD) modelljéről számoltak be [7].…”
Section: Eredeti Közleményunclassified
“…Metformin Due to multi-factorial mechanism of action of metformin, a multi-compartment PK-PD model of metformin for the treatment of type II diabetes mellitus is used as described in [9][10][11]. This model constitutes three compartments including the GI tract (gut), liver and periphery.…”
Section: Pharmacokinetic-pharmacodynamic Modeling Ofmentioning
confidence: 99%
“…For the oral administration, the pharmacokinetics of metformin from mouth to the GI lumen is described by the following equation: (9) where α and β are rate constants; A and B represent the contribution of the corresponding exponentials. These parameters were estimated by optimization using experimental data points in [9].…”
Section: Pharmacokinetic-pharmacodynamic Modeling Ofmentioning
confidence: 99%
See 1 more Smart Citation